A new Asian genus of the tribe Elicini (Hemiptera: Fulgoromorpha: Tropiduchidae) with two new species from Vietnam - Wang, Menglin; Stroiński, Adam; Bourgoin, Thierry; Zhang, Yalin (Zootaxa, 2015)
A new genus Connelicita gen. nov. with 2 new species (C. backyensis sp. nov. and C. haiphongensis sp. nov.) of Tropiduchidae Elicini from Vietnam are described and illustrated. The Chinese species C. lungchowensis (Chou et Lu, 1977) comb. nov. is transferred into this new genus from the genus Sassula (Nogodinidae). A key to species of the new genus distributed in North Vietnam and China (Guangxi) is provided.